AB0214 The trajectory of disease activity in rheumatoid arthritis in the first two years of treatment in an asian ra cohort. (12th June 2018) - Teo, C.; Koh, E.T.; Woo, C.M.; Tang, X.; Tan, J.; Lian, T.Y.; Koh, L.W.; Leong, K.P.
Abstract : Background: Response to disease-modifying antirheumatic drugs (DMARDs) is heterogenous. Clinical information and baseline characteristics do not allow reliable prediction of which trajectory patients will follow after DMARD initiation. Objectives: We analysed the change in disease activity over the first two years of treatment in rheumatoid arthritis (RA) to identify different treatment response patterns among RA patients initiating DMARDs. We wanted to establish a predictive model for identifying patients with different treatment response patterns. Methods: We selected patients from our prospective RA disease registry who have been treated for three months or fewer at study entry. We analysed the change of the disease activity, as defined by the DAS28–ESR, over the subsequent two years. A predictive model with parameters from three time points is proposed to stratify patients according to the outcomes. Results: We analysed the data from 179 patients over 1044 study visits. We discerned three groups of patients according to disease activity trajectories: 1 the first group (53%) has high DAS at study entry and approach remission after 18 months; 2 the second group (22%) has high DAS at entry that remained elevated throughout the study period; and, 3 the third group of patients (25%) started with moderately high DAS and reached remission after 3 months of treatment. Patients at risk of being in the third group can be identified using data from three time points, at initiation of DMARDs, at 3 months and at 6 months. Conclusions: RA patients showed three distinct disease activity trajectories with treatment. Our model can categorise patients into these groups. References: [1] Aga Ab, et al. Time trends in disease activity, response and remission rates in rheumatoid arthritis during the past decade: results from the NOR-DMARD study 2000–2010. Ann Rheum Dis2015;381–8. [2] Courvoisier DS, et al. Rheumatoid arthritis patients after initiation of a new biologic agent: trajectories of disease activity in a large multinational cohort study. EBioMedicine 2016;302–306. [3] Siemons L, Ten Klooster PM, Vonkeman HE, Glas CAW, Van de Laar MAF. J. Distinct trajectories of disease activity over the first year in early rheumatoid arthritis patients following a treat to-target strategy. Arthritis Care Res2014;66:625–630. [4] Aga Ab, et al. Time trends in disease activity, response and remission rates in rheumatoid arthritis during the past decade: results from the NOR-DMARD study 2000–2010. Ann Rheum Dis 2015, 381–8 [5] Courvoisier DS, et al. Rheumatoid arthritis patients after initiation of a new biologic agent: trajectories of disease activity in a large multinational cohort study. EBioMedicine 2016, 302–306 [6] Siemons, L., Ten Klooster, P. M., Vonkeman, H. E., Glas, C. A. W. & Van de Laar, M. a F. J. Distinct trajectories of disease activity over the first year in early rheumatoid arthritis patients following a treat to-target strategy. Arthritis Care Res.66, 625–630(2014) Disclosure of Interest: None declared